Parkinson's Disease Caregiver Strain in Singapore - Tan, Siok-Bee; Williams, Allison F.; Tan, Eng-King; Clark, Richard B.; Morris, Meg E. (Frontiers in Neurology, 2020)
Background Caregiver strain is recognized globally with Parkinson’s disease (PD). Comparatively little is understood about caregiver burden and strain in Asia. Objective To investigate caregiver strain for families living with PD in Singapore, in light of international data. Methods 94 caregivers were recruited via people living with idiopathic PD in Singapore. Caregiver strain was assessed using the Zarit Burden Interview (ZBI); health status was assessing using the Cumulative Illness Rating Scale for Geriatrics (CIRS-G). PD disability measures were the Unified Parkinson’s Disease Rating Scale (UPDRS) and modified Hoehn & Yahr (1967) Scale. Results Primary caregivers of people living with PD in Singapore were mostly cohabiting spouses, partners or offspring. Around half employed foreign domestic helpers. Mean caregiving duration was 5.9 years with an average of eight hours per day spent in caregiving roles. Most care providers were comparatively healthy. Caregivers reported significant levels of strain which increased with greater level of disability (r=0.36, n=94, p<0.001). Associations were significant between caregiver strain and scores on the UPDRS mentation, behaviour and mood subscales (r=0.46, n=94, p<0.001, 95% CI [0.28, 0.60]). High scores on the UPDRS activities of daily living subscale were associated with caregiver strain (r=0.50, n=94, p<0.001, CI [0.33, 0.64]). Conclusion Most caregivers in this Singapore sample reported high levels of strain, despite comparatively good physical function. Caregiver strain in PD spans geopolitical and cultural boundaries and correlates with disease severity. These results support the need for better early recognition, education and support for caregivers of people living with PD.